(untitled) (SCIENCE TIME JOURNAL, 2026)
This study explores the phraseographic characteristics of phraseological units operating within scientific discourse. It investigates the principles and techniques used to document, interpret, and systematize such units in lexicographic sources, paying special attention to their structural stability, semantic specificity, and functional roles in academic texts. The research analyzes how the distinctive nature of scientific discourse influences the selection and presentation of phraseological material. Additionally, it examines the interplay between phraseological meaning and scientific context, highlighting the contribution of these units to the structuring and conceptualization of specialized knowledge. Using a functional-discursive framework, the study applies contextual and comparative methods to reveal recurrent models of phraseographic representation in scientific discourse.